2013
DOI: 10.1017/s1368980013002917
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and weight status associated with behavioural problems in young children

Abstract: Objective: To investigate the associations of behavioural problems with dietary patterns and weight status in young children. Design: We assessed poor social skills and behavioural problems with a seventysix-item Preschool and Kindergarten Behavior Scale (PKBS) and found three dietary patterns ('Korean healthy', 'animal foods' and 'sweets') in food/food group intake data assessed by an FFQ and analysed using factor analysis. Multiple logistic regression analyses were used to assess the association of diet and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…Furthermore, the dietary assessment method used by Arvidsson et al (2017; a 43-item food frequency questionnaire) was different from that used in the current study. Also consistent with the current study results, Oh et al (2014) found a relationship between healthy dietary intake and better social skills in a study of 1,458 preschool children in Korea. However, this was based on cross-sectional data only.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the dietary assessment method used by Arvidsson et al (2017; a 43-item food frequency questionnaire) was different from that used in the current study. Also consistent with the current study results, Oh et al (2014) found a relationship between healthy dietary intake and better social skills in a study of 1,458 preschool children in Korea. However, this was based on cross-sectional data only.…”
Section: Discussionsupporting
confidence: 92%
“…Only a handful of cross-sectional studies have investigated the relationship between child dietary intake and socioemotional dimensions of school readiness. These studies have found that a healthy dietary intake was associated with better social skills among 5-year-old children (Oh et al, 2014) and that malnutrition was associated with impaired social behavior among 3-year-old children (Liu & Raine, 2017). Therefore, through improved nutrition and healthy weight status, it is plausible that healthy dietary intake in the early years could be beneficial for children's socioemotional development.…”
Section: Introductionmentioning
confidence: 99%
“…Pada anak- anak usia sekolah, terjadi perubahan pola makan yang besar. Kalau selama ini waktu makan mereka lebih banyak dilewatkan bersama orangtuanya, maka memasuki usia sekolah, kegiatan makan mereka lebih banyak dilewatkannya di sekolah bersama teman-temannya (7,23) . Status gizi yang baik dan buruk yang dialami anak usia sekolah merupakan pilihan dalam menentukan kesehatan dan kecerdasan mereka, maka diperlukan metode tatalaksana pola konsumsi terhadap status gizi anak.…”
Section: Pendahuluanunclassified
“…Additionally, maternal mental health, such as anxiety and depression is associated with the onset of child CP (Fairfield et al, 2019;Fong et al, 2019;Holmes, 2013;Shelleby & Shaw, 2014;Stein et al, 2014). Diet is another factor that has been shown to impact child CP, both as a buffer and exacerbator (Gajos & Beaver, 2016;Gete et al, 2022;Miyake et al, 2020;Oh et al, 2014;Prado & Dewey, 2014;Zhu et al, 2023).…”
Section: Factors Impacting Conduct Problems Across Developmentmentioning
confidence: 99%
“…Children who are exposed to an 'unhealthy' diet antenatally by mothers and postnatally by their own food consumption may be at a higher risk for behavioural problems. Whereas a healthier diet may be a protective factor for children's behaviour (Ajmal et al, 2022;Dou et al, 2023;Gete et al, 2022;Hammersley et al, 2022;Jacka, 2019;Jackson et al, 2016;Miyake et al, 2020;Oh et al, 2014;Zhang et al, 2021;Zhu et al, 2023). It asks the question on whether diet is important to consider when investigating potential preventative measures to combat negative child outcomes, such as CP.…”
Section: Diet Aggression and Child Conduct Problems -Introductionmentioning
confidence: 99%